REAKTULISASI DAN PENGEMBANGAN MODEL PELESTARIAN BARONGSAI SEBAGAI MODAL SOSIAL HARMONI MULTIETNIS DI SURAKARTA - Riyadi, Riyadi; Hermawan, Eko Satriya; Pelu, Musa; Wibowo, Guntur Arie (Program Studi Pendidikan Sejarah - Universitas Samudra, 2022)
The problem that arises in this research is how to make a pattern in the form of a prototype / model of lion dance so that it is always present not only in annual rituals such as Chinese New Year, but can live throughout the year by optimizing the lion dance for the benefit of rituals, rituals, tourism, entertainment, and sports. sports, considering that most of the players are Javanese so that Javanese and Chinese can blend naturally within the framework of multicultural life, which is achieved by the development of one of the Chinese cultures, especially the performing arts of Barongsai which is expected to be able to improve the economy of the people of Surakarta in the tourism sector (ecotourism). From the problems above, the following questions can be formulated: First, to what extent is the lion dance developed outside the interests of traditional rituals?; Second, to what extent is the appreciation of the public and the government for using the lion dance in various interests?; Third, how to formulate a development model that allows accommodation of the lion dance function as a ritual, tourism, entertainment, and sport, in an integrated manner?; and Fourth, how are stakeholder and stakeholder responses that can be done in FGD and expert judgment. With strong multicultural social stability, various positive impacts in the economic and cultural tourism fields can be formed. In the development of the lion dance performance, it is very important to develop synergistically the integration of Ritual, Tourism, Entertainment, and Sports.